1994
DOI: 10.1088/0953-8984/6/20/002
|View full text |Cite
|
Sign up to set email alerts
|

The structural properties of liquid and quenched sulphur II

Abstract: Neutron diffraction experiments over the momentum transfer range 0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
35
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 14 publications
8
35
0
2
Order By: Relevance
“…The S-S third neighbor distance in the orthorhombic a-sulfur crystal, c-S 8 , is 4.471 Å , while the fourth neighbors are situated at 4.718 Å . Similar feature was also observed in liquid sulfur below the polymerization transition, i.e., consisting of sulfur rings [23,24]. Consequently, the 4.5 Å peak was attributed to a weighted average of the 3rd and 4th neighbor distances in the sulfur rings.…”
Section: Neutron and High-energy X-ray Diffractionsupporting
confidence: 70%
“…The S-S third neighbor distance in the orthorhombic a-sulfur crystal, c-S 8 , is 4.471 Å , while the fourth neighbors are situated at 4.718 Å . Similar feature was also observed in liquid sulfur below the polymerization transition, i.e., consisting of sulfur rings [23,24]. Consequently, the 4.5 Å peak was attributed to a weighted average of the 3rd and 4th neighbor distances in the sulfur rings.…”
Section: Neutron and High-energy X-ray Diffractionsupporting
confidence: 70%
“…This transition is believed to be due to the formation of long chains of sulphur atoms at the higher temperature. Yet the density barely changes in the transformation, (0.0335 atoms/Å 3 before to 0.0332 atoms/Å 3 after) and the diffraction patterns for sulphur in these two different states are almost identical [137]. Hence diffraction from a disordered material cannot by itself necessarily tell us the state of the material, unlike crystalline phases, where each phase has a distinct sequence of Bragg peaks.…”
Section: The Nature Of the Structural Transition In Watermentioning
confidence: 99%
“…Other neutron diffraction studies from the same group have also demonstrated structural differences between the liquid and the quenched solid. 13 This difference has been considered as arising from the existence of broken bonds in the quenched state. This unequivocally shows that depolymerization can occur during the quenching procedure.…”
mentioning
confidence: 99%